Effect of Grade I and II Intraventricular Hemorrhage on Visuocortical Function in Very Low Birth Weight Infants - Madan, Ashima (Seeing Perceiving, 2012)
The neurological outcome for infants with Grade I/II intraventricular hemorrhage (IVH) is debated. The aim of this study was to determine whether very low birth weight infants (VLBW, < 1500 g) with Grade I /II (IVH) have altered visuocortical activity compared with infants with no IVH. We assessed the quantitative swept parameter Visual Evoked Potential (sVEP) responses evoked by three different visual stimuli. Data from 52 VLBW infants were compared with data from 13 infants with Grade I or II IVH, enrolled at 5 – 7 months corrected age. Acuity thresholds and suprathreshold response amplitudes were compared. Grating Acuity (GA), Contrast Sensitivity (CS) and Vernier Acuity (VA) were each worse in the Grade I/ II IVH compared with the no IVH groups (8.24 cpd in IVH group vs 13.07 cpd in no IVH group for GA; 1.44% vs 1.18% for CS and 1.55 arcmin vs 0.58 arcmin for VA). The slopes of the response amplitude for CS and VA were significantly lower in IVH infants. The spatial frequency tuning function was shifted downward on the spatial frequency axis, without a change in slope. These results indicate that Grade I/II IVH are associated with deleterious effects on cortical vision development and function.